The Urgency of Financial Literacy in Hajj Funds Management for Indonesian Muslims - Sarka, Susi Indriani; Osman , Ahmad Zamri; Annuar , Hairul Azlan (Journal of Islamic Economics and Finance Studies, 2024)
It was not widely known by the public that the cost of performing the hajj exceeded the predetermined Cost of the Hajj Travel (Biaya Perjalanan Ibadah Haji/BIPIH) set by the government. Although the government plays a role in subsidizing the cost of pilgrimage organizing (Biaya Penyelenggaraan Ibadah Haji/BPIH), the actual calculation is never shared with the public, leaving many in the dark. Indonesian Muslims must be educated about the importance of financial literacy. This article aims to provide a comprehensive understanding of Hajj, shedding light on the Muslim perspective in Indonesia regarding Hajj and its management. This comprehension will empower the community to approach matters with reason and facilitate their involvement in monitoring the management of Hajj funds. The concept of Hajj's financial literacy aims to address the communication gap in managing Hajj funds. The proposed solution is continuous education and stimulation actions that functioned in fostering a sense of novelty and raising public trust in the community. The Ministry of Religion, the Ministry of Education, and community-accessible institutions such as the police (e.g., Babinsa) and Indonesian National Army (Tentara Nasional Indonesia/TNI), as well as religious leaders, mass organizations, and other members of society, should work together to shift society's mindset.